2021
DOI: 10.1021/acs.macromol.1c00990
|View full text |Cite
|
Sign up to set email alerts
|

Toward Taming the Chemical Reversibility of Perfluoropyridine through Molecular Design with Applications to Pre- and Postmodifiable Polymer Architectures

Abstract: Polymer functionality greatly determines many of the key properties of these materials, such as glass-transition temperature, electrical and thermal conductivity, thermal stability, mechanical strength, and processability. Despite the importance of polymer functionality in determining material properties, the synthesis of functional polymers, with well-defined molecular weights and compositions, can still present a significant challenge, with many of the methods related to pre- or postpolymerization modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The reversibility was also seen when attempts to post-functionalize poly38 with the various ROH nucleophiles resulted in densely cross-linked polymer. DFT calculations, along with the experimental observations on the monomers utilized in this study, support that the reversibility of 38 could be attributed to having a small dihedral angle [75]. By reacting the terminal alkenes of these monomers with hydride-terminated polydimethylsiloxanes (H-PDMSs), linear silicon-based elastomers and oils were obtained.…”
Section: Perfluoropyridine Used In Polymers and Materialssupporting
confidence: 63%
See 3 more Smart Citations
“…The reversibility was also seen when attempts to post-functionalize poly38 with the various ROH nucleophiles resulted in densely cross-linked polymer. DFT calculations, along with the experimental observations on the monomers utilized in this study, support that the reversibility of 38 could be attributed to having a small dihedral angle [75]. By reacting the terminal alkenes of these monomers with hydride-terminated polydimethylsiloxanes (H-PDMSs), linear silicon-based elastomers and oils were obtained.…”
Section: Perfluoropyridine Used In Polymers and Materialssupporting
confidence: 63%
“…Later, in 2021, Houck et al demonstrated the ability to prepare a variety of aryl ether-functionalized polymers using both pre- and post-functionalized approaches [ 75 ]. In order to accomplish this, the authors initially prepared three monomers capable of undergoing ring-opening metathesis polymerization (ROMP) ( Scheme 26 ) [ 75 ]. Compounds 37 and 38 had been previously reported [ 76 ].…”
Section: Perfluoropyridine Used In Polymers and Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perfluoroaromatics are a privileged scaffold in organofluorine chemistry, often used in the production of various drugs, agrochemicals, and high-performance fluoropolymers [1][2][3]. Fluoropolymers, particularly those with fluoroaromatics in their architectures, are widely known for their desirable properties such as chemical resistance, thermal stability, and solution and melt processability [3][4][5][6]. Fluoroaromatics have also shown great promise for use in biomedical applications [7][8][9][10], including as substituents to allow medications to more easily cross the blood brain barrier [11,12] and penetrate cells [13].…”
Section: Introductionmentioning
confidence: 99%